ANALISIS TINGKAT PENCEMARAN AIR DENGAN METODE INDEKS PENCEMARAN DI TELUK YOUTEFA, JAYAPURA, PROVINSI PAPUA - Janviter Manalu; I Wayan Nurjaya; Surjono HS; Kholil Kholil (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Youtefa Bay is one of the potential natural recources, is located on the western side of Jayapura City,Papua province.The waters has beenutilized for fishery, transportation and ecotourisme.Youtefa Bay surroundings are settlements where the most of residents are fishermen and farmers.The aim of this study is to determine the pollution level of the Youtefa Bay,approached by pollution index method.The results showed that the water condition of Youtefa Bay was slightly to moderately polluted.Due to pollution, it is therefore very importance to periodically monitor the water quality of the Youtefa Bay to maintain its sustainability.